Effectiveness of Using Pianica in Music Arts Learning at SDN 1 Mijen - Taqiya, Izza; Sari, Fauziyah Kemala; Wijayanto, Wasis (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: Music education in elementary schools is an essential component of holistic child development, contributing to students’ character formation, creativity, motor coordination, and emotional intelligence. However, the implementation of music learning is often suboptimal due to the limited availability of instructional tools and the lack of engaging teaching methods. This study aims to explore the effectiveness of using the melodica (locally known as pianika) as a concrete and accessible musical instrument to improve students' engagement and understanding in music education. Research Methods: Conducted at SD N 1 Mijen, this research uses a descriptive qualitative approach involving participatory observation, semi-structured interviews with a music teacher and six fourth-grade students, and documentation of the learning process. Finding/Results: The findings indicate that the use of the melodica increases student motivation, enhances comprehension of basic musical notation, and supports the development of performance confidence. Teachers reported that the pianika facilitates structured, step-by-step learning and provides an effective means of formative assessment through direct practice. Students responded positively, becoming more active and enthusiastic during lessons. Additionally, the instrument allowed students to express themselves musically in a collaborative and supportive environment. These results suggest that simple musical instruments like the pianika can serve not only as effective learning tools but also as media that foster emotional and social development. Conclusion: This study supports the integration of practical, engaging, and multimodal strategies in elementary music education to enhance learning outcomes and student participation.